2017
DOI: 10.1007/s10529-017-2287-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: The use of natural infochemicals for sustainable and efficient harvesting of the microalgae Scenedesmus spp. for biotechnology: insights from a meta-analysis

Abstract: Unfortunately, data in Fig. 4 became illegible as the figure is compressed during the initial stage of processing. The correct Fig. 4 with data clarity is shown below: The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A summary of the current literature reports on characterization of infochemicals is provided in Table 1. A metaanalysis of existing studies highlighted grazer-specific effects that can reach similar magnitudes to metal salts and suggested that a clear distinction between coenobia formation and aggregationbased mechanisms is necessary (Roccuzzo et al, 2016). This knowledge has largely arisen from experiments measuring dose-dependent production of colonies and aggregates, but we still know too little about how infochemicals trigger the physiological and cellular level changes that underpin colony formation and flocculation.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the current literature reports on characterization of infochemicals is provided in Table 1. A metaanalysis of existing studies highlighted grazer-specific effects that can reach similar magnitudes to metal salts and suggested that a clear distinction between coenobia formation and aggregationbased mechanisms is necessary (Roccuzzo et al, 2016). This knowledge has largely arisen from experiments measuring dose-dependent production of colonies and aggregates, but we still know too little about how infochemicals trigger the physiological and cellular level changes that underpin colony formation and flocculation.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is to explore the control of the zooplankton and ways to avoid the grazing in the cultivation with the aquaculture effluent. A single Scenedesmus genotype has the ability to produce one or more alternative morphologies, including colonies, in response to environmental conditions (e.g., zooplankton grazing) [31]. The Scenedesmaceae could have been able to defend themselves from zooplankton grazing thanks to this ability, leading to their dominance in the microalgal community after the grazing of C. vulgaris.…”
Section: Cultivation Of Chlorella Vulgaris With Unsterilized Aquacultmentioning
confidence: 99%